An 18-week multimodal training program improves functional autonomy in elderly women with reduced functional autonomy (Research, Society and Development, 2022)
Introduction: The aging process brings natural losses to the elderly, which can lead to deficits in functional autonomy, which can be minimized with regular physical exercise. Objective: To evaluate the effects of 18 weeks of a multimodal training program in elderly women with reduced functional autonomy. Materials and methods: Refers to a longitudinal study, of a quantitative nature, with a sample composed of 12 elderly women. The multimodal training lasted 18 weeks with 3 weekly sessions. The functional autonomy of the elderly was assessed through the functional assessment protocol of the Latin American Development Group for Maturity (GDLAM), consisting of the following tests: walking 10 meters (C10m); getting up from a sitting position (LPS); getting up from the prone position (LPDV); get up from the chair and move around the house (LCLC). The general index of the GDLAM (GI) was calculated. For data analysis, normality was verified (Kolmogorov-Smirnov), and Student's T test was used, considering a significance level of p